Management of Dengue Shock Syndrome A Prospective Study - H. Tjandra (Indonesian Pediatric Society, 1991)
Since dengue hemorrhagic fever (DHF) was first reported 20 years ago, the only serious variant of the disease, dengue shock syndrome (DSS), still continues to cause a relatively high mortality. An effective yet simple management of DSS which can be carried out in every hospital is certainly necessary if the dead toll is ro be reduced. Prospective study of a simple procedure in managing DSS patients in Bhayangkara Police Hospital Kediri is reported. Depends on the severity of the disease, for DHF grade III: 20 mL/kg bw Lactated - Ringer solution was given at free rare. This is followed by 20 mL/kg bw of synthetic plasma expander (expafusin) in a rate of thrice tire body weight and continued with lactated-ringer and 5% dextrose in I 12 Saline alternately with a rate of twice the body weight per minute for the remaining first 14 hours. For DHF grade IV, the same fluids were given, except for the amount and the infusion rate. Drugs administered and medical care were all the same/or both groups. A close observation, a critical assessment, and an accurate as well as a rapid action are very important factors. Totally there were 11 S patients of which 8 died. The mortality rate was 7%. A better management and/or treatment has to be developed 10 further reduce the mortality.